FORMATION OF IDEOLOGICAL IMMUNITY OF STUDENTS ON THE BASIS OF EDUCATIONAL CORRECTIONAL ACTIVITY - Bozorova Muazzam Hamid qizi (European Journal of Humanities and Educational Advancements, 2023)
In this article, thoughts and reflections on the formation of ideological immunity of students on the basis of educational Correctional activities are kept. While the main task of education is to arm students with knowledge, skills and qualifications, upbringing consists in the content of beliefs, moral qualifications and skills, needs and aspirations that correspond to the rules of etiquette adopted in society in the younger generation. Every specialist engaged in upbringing should first of all be able to clearly imagine his activities and the goal envisaged in him, understand the importance of this goal. So, it is very important in this process to imagine from the very beginning the questions of what kind of person should be brought up must, what a person should be as a result of upbringing